2003
DOI: 10.1128/jb.185.2.489-495.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Secretion Determinants of theBordetella pertussisBrkA Autotransporter

Abstract: The autotransporters comprise a functionally diverse family of gram-negative proteins that mediate their own export across the bacterial outer membrane. They consist of an amino-terminal passenger region called the "␣-domain" and the structural hallmark of the autotransporter family, a carboxy-terminal transporter region usually referred to as the "␤-domain." The passenger region can be quite diverse and constitutes the effector functions of these proteins, whereas the C-terminal region is conserved and is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 40 publications
3
64
0
2
Order By: Relevance
“…In homologous proteins, this region has previously been designated the autotransporter junction region and has been suggested to play a role in secretion (25)(26)(27)(28). Ohnishi et al (26) have shown that nonsecreted deletion mutants in the junction region of SSP, an autotransporter from Serratia marcescens, could be rescued for secretion when the junction region is supplied in trans.…”
Section: Generation Of Linkermentioning
confidence: 99%
“…In homologous proteins, this region has previously been designated the autotransporter junction region and has been suggested to play a role in secretion (25)(26)(27)(28). Ohnishi et al (26) have shown that nonsecreted deletion mutants in the junction region of SSP, an autotransporter from Serratia marcescens, could be rescued for secretion when the junction region is supplied in trans.…”
Section: Generation Of Linkermentioning
confidence: 99%
“…Oliver et al (364,365) recently discovered an autochaperone domain in BrkA. This well-conserved domain, found upstream of the translocation unit, is present within the passenger domains of several autotransporters, like AIDA-I, IgA1 protease, Ag43, Hap, and IcsA, but was not detected in some autotransporters such as TcfA and Hia (365).…”
Section: Autotransporter Secretion Pathway (Type Va)mentioning
confidence: 99%
“…However, the passenger domain is not necessarily cleaved but may also remain intact as a large protein with a membrane-bound C-terminal domain and an N-terminal domain extending into the external milieu, e.g., Hia or Hsr (367,465). Nevertheless, the cleavage between the passenger domain and the translocation unit can occur either well upstream of the linker region or within the predicted ␣-helical region, like BrkA (364). In this latter case, BrkA remains steadfastly associated with the bacterial outer membrane, raising the possibility that the linker region could also act as an anchor for the passenger domain.…”
Section: Autotransporter Secretion Pathway (Type Va)mentioning
confidence: 99%
See 2 more Smart Citations